The burden of tuberculosis disease in women, Colombia 2010-2018 - Laura Plata-Casas (Asociación Colombiana de Infectología, 2023)
Objective: to estimate disability-adjusted life years in women attributable to tuberculosis in Colombia 2010-2018. Methods: A retrospective descriptive study was conducted. The following variables were studied: year of occurrence, age groups and origin. This study included 41,354 women who consulted in the hospital network and 2530 cases of mortality in women, registered in the country's vital statistics system. Using the abbrevia-ted methodology proposed by the World Health Organization for measuring the burden of disease BD, years of life lost, years of life with disability and years of healthy life lost by women at the subnational level were estimated. Results: The Disability-Adjusted Life Years rate for the study period was 427.2 (95% II 353-492.3) per 100,000 women. Women of reproductive age (10 to 49 years old) account for 57.9 per cent of these. Departments such as Amazonas 1,426 (725.4-2,541.4) and Guajira 1,001.1 (693.3-1,260) had the highest rates (per 100,000 inhabitants). Twelve territorial entities have an increasing burden of disease. Conclusions: The rate of disability-adjusted life years due to tuberculosis in women for nine years was high and presents subnational differences perhaps due to large social or economic gaps or deficits in institutional or programmatic capacities.